Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Tematik Kelas III SD Negeri 104201 Kolam Tahun Ajaran 2022/2023 - Khoiriyah Hasibuan, Nurul (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The problem in this study is the low learning outcomes in thematic learning, especially theme 2 loving plants and animals, and sub-theme 2 the benefits of animals for human life. This study aimed to improve student learning outcomes by applying the Role Playing learning model to theme 2 loving plants and animals, and sub-theme 2 the benefits of animals for human life. This type of research is